2015
DOI: 10.1074/jbc.m115.684076
|View full text |Cite
|
Sign up to set email alerts
|

Two-pore Channels (TPC2s) and Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) at Lysosomal-Sarcoplasmic Reticular Junctions Contribute to Acute and Chronic β-Adrenoceptor Signaling in the Heart

Abstract: Background: The Ca2+-releasing messenger nicotinic acid adenine dinucleotide phosphate (NAADP) acts via lysosomal two-pore channels (TPC2).Results: Tpcn2−/− cardiac myocytes showed reduced acute responses to β-adrenoreceptor stimulation and chronically reduced cardiac hypertrophy and arrhythmogenesis.Conclusion: Acute and chronic effects of cardiac β-adrenoreceptor stimulation depend on NAADP acting via TPC2 in lysosomes.Significance: NAADP/TPC2 signaling pathways offer new strategies for cardiac therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
128
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(152 citation statements)
references
References 62 publications
13
128
0
Order By: Relevance
“…Indeed, expression of both isoforms, but particularly of TPC2, was much more pronounced in the embryo than in the adult. Recent studies of TPC knockout mice have shown them to have abnormalities in smooth muscle contraction (Tugba Durlu-Kandilci et al, 2010), receptor trafficking and endolysosomal function , storage and utilization of cholesterol by the liver (Grimm et al, 2014), angiogenesis (Favia et al, 2014), skeletal muscle function (Cang et al, 2013, brown adipose tissue thermogenesis (Lear et al, 2014) and heart contraction in response to b-adrenergic stimulation (Capel et al, 2015). Although these abnormalities may reflect defects in the signalling pathways regulating physiological responses in the affected tissues, it is also possible that they are due to disturbances of TPC expression during development.…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 99%
“…Indeed, expression of both isoforms, but particularly of TPC2, was much more pronounced in the embryo than in the adult. Recent studies of TPC knockout mice have shown them to have abnormalities in smooth muscle contraction (Tugba Durlu-Kandilci et al, 2010), receptor trafficking and endolysosomal function , storage and utilization of cholesterol by the liver (Grimm et al, 2014), angiogenesis (Favia et al, 2014), skeletal muscle function (Cang et al, 2013, brown adipose tissue thermogenesis (Lear et al, 2014) and heart contraction in response to b-adrenergic stimulation (Capel et al, 2015). Although these abnormalities may reflect defects in the signalling pathways regulating physiological responses in the affected tissues, it is also possible that they are due to disturbances of TPC expression during development.…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 99%
“…Their functions have been shown to be involved in various physiological processes, such as endocytosis and endosomal trafficking (5, 6), lysosomal morphology and pigmentation (7,8), autophagy (9, 10), and nutrient metabolism via the mammalian target of rapamycin (mTOR) complex (11). Not surprisingly, given their central physiological role, defects in TPC channels are associated with a variety of disabling human disorders (9,(12)(13)(14)(15)(16)(17).Despite their physiological importance, some biophysical properties of mammalian TPC channels are still under debate (18). Mammalian TPC channels were initially identified as receptors of nicotinic acid adenine dinucleotide phosphate (NAADP), a Ca 2+ -mobilizing second messenger, and responsible for Ca 2+ release from the acidic organelles (19)(20)(21).…”
mentioning
confidence: 99%
“…Their functions have been shown to be involved in various physiological processes, such as endocytosis and endosomal trafficking (5, 6), lysosomal morphology and pigmentation (7,8), autophagy (9, 10), and nutrient metabolism via the mammalian target of rapamycin (mTOR) complex (11). Not surprisingly, given their central physiological role, defects in TPC channels are associated with a variety of disabling human disorders (9,(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Previous studies regarding CaMKII in the nervous system and heart have resulted in its functions being well characterized [38-40]. Accumulated evidence has shown that CaMKII activation is closely related to increased intracellular calcium levels [8, 9].…”
Section: Discussionmentioning
confidence: 99%